All‐Solid‐State Batteries: Digital Twin‐Driven All‐Solid‐State Battery: Unraveling the Physical and Electrochemical Behaviors (Adv. Energy Mater. 35/2020). Issue 35 (15th September 2020) - Park, Joonam; Kim, Kyu Tae; Oh, Dae Yang; Jin, Dahee; Kim, Dohwan; Jung, Yoon Seok; Lee, Yong Min
Abstract : In article number 2001563 Yoon Seok Jung, Yong Min Lee and co‐workers build a highly sophisticated digital twin‐driven all‐solid‐state battery with a solid sulfide electrolyte. Digital twindriven batteries, which are stacked by digital voxels and modeled with mathematic equations for multi‐physics, are utilized as a key platform for designing electrodes or cells, predicting electrochemical behavior, analyzing invisible defects in the cell, and discovering new insights to improve the performance of the cell.